Children’s Clothing Virtual Simulation Immersive Design and Show Based on Machine Learning - Dai Jingyu (Hindawi Limited, 2021)
In view of the inconvenient display of children’s clothing, the poor experience of designers when modifying sample clothes, and the immature display of children’s clothing, which affects the rational judgment of fashion buyers, this paper puts forward the modular design method of children’s clothing virtual fitting. This research uses Lectra CAD software to make children’s clothing pattern, Clo3D for virtual modular design, and “Insanda children’s clothing virtual design and show” for virtual try-on and show. The simulation results show that the research can effectively improve the efficiency of designers and buyers, can save costs, and can be effectively applied in the commercial field. At the same time, it provides a practical basis for the development of children’s clothing virtual display technology and the formulation of standards related to children’s clothing in the future.